Contributions of the international plant science community to the fight against infectious diseases in humans—part 2: Affordable drugs in edible plants for endemic and re‐emerging diseases. Issue 10 (19th July 2021) - He, Wenshu; Baysal, Can; Lobato Gómez, Maria; Huang, Xin; Alvarez, Derry; Zhu, Changfu; Armario‐Najera, Victoria; Blanco Perera, Aamaya; Cerda Bennaser, Pedro; Saba‐Mayoral, Andrea; Sobrino‐Mengual, Guillermo; Vargheese, Ashwin; et al.
Summary: The fight against infectious diseases often focuses on epidemics and pandemics, which demand urgent resources and command attention from the health authorities and media. However, the vast majority of deaths caused by infectious diseases occur in endemic zones, particularly in developing countries, placing a disproportionate burden on underfunded health systems and often requiring international interventions. The provision of vaccines and other biologics is hampered not only by the high cost and limited scalability of traditional manufacturing platforms based on microbial and animal cells, but also by challenges caused by distribution and storage, particularly in regions without a complete cold chain. In this review article, we consider the potential of molecular farming to address the challenges of endemic and re‐emerging diseases, focusing on edible plants for the development of oral drugs. Key recent developments in this field include successful clinical trials based on orally delivered dried leaves of Artemisia annua against malarial parasite strains resistant to artemisinin combination therapy, the ability to produce clinical‐grade protein drugs in leaves to treat infectious diseases and the long‐term storage of protein drugs in dried leaves at ambient temperatures. Recent FDA approval of the first orally delivered protein drug encapsulated in plant cells to treat peanut allergy has opened the door for the development of affordable oral drugs that can be manufactured and distributed in remote areas without cold storage infrastructure and that eliminate the need for expensive purification steps and sterile delivery by injection.